2010
DOI: 10.5012/bkcs.2010.31.9.2531
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study on Triphenylamine-based Dye Sensitizers Containing Different Donor Moieties

Abstract: Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations have been employed to investigate the molecular structures and absorption spectra of two dyes containing diphenylaniline and 4-diphenylamino-diphenylaniline as donor moiety (TPA1 and TPA3). The geometries indicate that the strong conjugation is formed in the dyes. The electronic structures suggest that the intramolecular charge transfer from the donor to the acceptor occurs, and the electron-donating capability of 4-diphenylamino-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…TPA and its derivatives have been used as photoactive molecules during several decades and their applicability in the construction of DSSCs is also of technological interest. [29][30][31][32][33][34] . The molecules were considered in several experimental and (TD)DFT computational studies related to the mHJ approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPA and its derivatives have been used as photoactive molecules during several decades and their applicability in the construction of DSSCs is also of technological interest. [29][30][31][32][33][34] . The molecules were considered in several experimental and (TD)DFT computational studies related to the mHJ approach.…”
Section: Introductionmentioning
confidence: 99%
“…TPA is able to confine cationic charge and hamper aggregation between molecules, which induces self-quenching and reduces the electron injection efficiency. [31,33] On the other hand, C60 is an excellent electron donor [35][36][37][38] that can react with a variety of chemical agents. [39][40][41][42][43][44] Recently, based on electrochemical and photophysical studies, Echegoyen et al [45] determined kct for the TPA-C60 and TPA-Sc3N@Ih-C80 donor-acceptor conjugates and showed that (i) ultrafast charge separation (CS) reactions occur at the molecular interface, thus giving evidence of CT activity; (ii) TPA-Sc3N@Ih-C80 generates longer-lived photoinduced charge transfer states (CTSs) than does TPA-C60; (iii) increasing the distance of the donor-acceptor interface produces longer-lived CTSs; (iv) nonpolar solvents bring about lack of CT activity; on the contrary, more polar solvents can slow down the charge recombination (CR) reaction; (v) a smaller value of kct for the CR reaction with Sc3N@Ih-C80 in comparison with C60 was found, which was attributed to a smaller value of the driving force.…”
Section: Introductionmentioning
confidence: 99%
“…The need to enhance the light-harvesting properties of organic dyes has motivated the search for the ideal donor [7][8][9][10] and acceptor [11][12][13][14][15][16][17] groups, the optimum manner to chemically connect them, [7][8][9] and the effect of chemical substitutions in distinctive molecular positions. [7,[39][40][41] These investigations are mainly based on analysis of the relative efficiencies among small sets of sensitizers. In general, it is hard to find systematic studies on the main characteristics of donor, acceptor, and pbridge constituents, which would be very helpful to catalogue the molecular fragments according to their characteristics when assembled as constituents of molecular dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Spectra of all newly designed systems were red shifted as compared to TC4 due to the small energy gap resulting from better conjugation and an electron withdrawing atom on the π-spacer. 29,30 Major absorption peaks of new systems exist between 423 and 456 nm. HOMO to LUMO transition is the most probable and lowest energy transition of all systems except system 3 and 4, for which HOMO-1 to LUMO is Systems with a stronger electron-donating auxiliary group (-OCH 3 ) (systems 2, 4, 6, 8 and 10) showed slight redshifted absorption relative to other systems which contain -CH=C(CH 3 ) 2 .…”
mentioning
confidence: 99%